Group Exhibition-erra Mediterranean in Crisis Municipal Cultural Center - Antoniou, Klitsa (My University, 2026)
Terra Mediterranean in Crisis Municipal Cultural Center. Nicosia, Cyprus Curated by Yiannis Toumazis